Legal principles for the drafting of a criminal policy against corruption in a constitutional State under the rule of law - Rojas Velásquez, Jeremías (2021)
This article proposes the development of a comprehensive criminal policy against corruption based on supranational and national legal principles within the framework of the constitutional rule of law. The objective of this proposal is to reinforce the legitimacy of the State and the unrestricted respect for fundamental rights.